Teaching software development of Electrical Machinery & Towage based on MATLAB GUI - Zhenxing Liu; Biao He; Bin Cai (2011 International Conference on Multimedia Technology, 2011)
According to the course teaching features and its' fundamentality in electric specialized subject of Electrical Machinery & Towage, a visual teaching software is developed based on MATLAB GUI. This paper provides a detailed introduction of the software's function and illustrates the theory and scheme of the design. The graphical interfaces design of static and dynamic characteristics for DC motor is illustrated as an example, and the visual effect is helpful to the course teaching.